Safety of fertility treatments in women with systemic autoimmune diseases (SADs). Issue 9 (2nd September 2019) - Vanni, VS; De Lorenzo, R; Privitera, L; Canti, V; Viganò, P; Rovere-Querini, P
ABSTRACT: Introduction : Systemic Autoimmune Diseases (SADs) include systemic lupus erythematosus, antiphospholipid antibody syndrome, rheumatoid arthritis, systemic sclerosis, Sjogren's syndrome, mixed connective tissue disease, idiopathic inflammatory myopathies and vasculitis. SADs often occur in women of childbearing age and can affect fertility. Both infertility treatments and fertility preservation techniques are thus often indicated. Areas covered : The literature regarding the safety of fertility-related drugs for both fertility preservation and infertility treatment in patients affected by SADs was reviewed. Based on current knowledge, all the options for fertility preservation should be contemplated in patients with SADs who are at risk for fertility loss, including GnRH analogue administration, oocyte/embryo vitrification and ovarian tissue cryopreservation. Similarly, if pregnancy is not contraindicated in a patient with a SAD, neither should be any fertility treatment. Expert opinion : Women with SADs should postpone conception until a stable disease has been achieved for at least 6 months. When infertility treatments are needed, women with antiphospholipid antibodies should receive concomitant anticoagulation. If in vitro fertilization/intra-cytoplasmic sperm injection and embryo transfer is required, ovarian hyperstimulation and the inherent risk of thrombosis should be eliminated by GnRH-agonist trigger and cycle segmentation. Counselling about adherence to anti-rheumatic therapy to prevent disease exacerbations is also critical.